2017
DOI: 10.1111/liv.13594
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, determinants and outcomes of pregnancy‐associated hepatitis B flares: A regional hospital‐based cohort study

Abstract: Pregnancy-associated hepatitis B flare occurred in 14% during pregnancy and 16% post-delivery and rarely led to hepatic decompensation. Positive HBeAg was the main risk factor identified. Women did not have adequate HBV monitoring or follow-up during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Studies showed 5.2%-9% of HBV carriers could have ≥2 log 10 increase in DNA levels during pregnancy. 17,18 A mean 0.4 log 10 increase in late pregnancy or in the early postpartum period was observed. 16 However, significant change in the antenatal viral load was not demonstrated in other studies; 19,20 our finding was consistent with the latter in that the viral load did not change significantly during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Studies showed 5.2%-9% of HBV carriers could have ≥2 log 10 increase in DNA levels during pregnancy. 17,18 A mean 0.4 log 10 increase in late pregnancy or in the early postpartum period was observed. 16 However, significant change in the antenatal viral load was not demonstrated in other studies; 19,20 our finding was consistent with the latter in that the viral load did not change significantly during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Previous evidence on the change of HBV DNA levels throughout pregnancy was conflicting. Studies showed 5.2%‐9% of HBV carriers could have ≥2 log 10 increase in DNA levels during pregnancy . A mean 0.4 log 10 increase in late pregnancy or in the early postpartum period was observed .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported rates of ALT flares postpartum are variable owing to different definitions of ALT flare, patient characteristics, and antiviral therapy (Table ). Studies from our group (N = 138; 60% Asian, 30% African) and other retrospective studies conducted in the United States and Australia (N = ~100; ~80% Asian) have reported hepatic flares during late pregnancy and early postpartum, even in the absence of antiviral treatment . ALT flares are reported to be more common in HBeAg+ carriers versus women with HBeAg− CHB.…”
Section: Epidemiology Of Hbv and Mtctmentioning
confidence: 59%